Emotional and Behavioral Problems in Youth with Autism: High Prevalence and Impact on Functioning. Issue 3 (21st April 2022) - Fombonne, Eric; Croen, Lisa A.; Bulkley, Joanna E.; Varga, Alexandra M.; Daida, Yihe G.; Hatch, Brigit A.; Dickerson, John F.; Lynch, Frances L.
Abstract : This article has supplementary material on the web site: www.jdbp.org . ABSTRACT: Objective: Emotional and behavioral problems (EBPs) may co-occur with autism spectrum disorder (ASD) and impair children's functioning beyond autism symptomatology. We compared the prevalence of EBPs in youths with or without ASD and evaluated their unique contribution to impairment in ASD. Methods: We surveyed 1267 children (79.4% boys, mean age: 9.2 years, range: 3–17) recruited at 3 sites in Kaiser Permanente and OCHIN primary care clinical networks, with confirmed International Classification of Diseases-10th ed. diagnosis of ASD (N = 564), asthma (N = 468), or neither (N = 429). Children from the 2 comparison groups were age-matched and sex-matched to the ASD group. EBPs and impairment were measured by the Strengths and Difficulties Questionnaire and autism symptomatology by the Social Responsiveness Scale in the ASD group only. Results: EBPs and impairment mean scores were significantly ( p < 0.001) higher in participants with ASD compared with children from the 2 comparison groups, across sexes and age groups, with no significant difference between the asthma and control groups. Among children with ASD, both EBPs and autistic symptoms were significantly correlated with impairment ( r = 0.64 and r = 0.65, respectively) and explained a significant proportion of impairment variance ( R 2 = 0.525; p < 0.001) in multiple linear regression. In the relative importance analysis, EBPs and autistic symptoms explained comparable proportions of impairment variance (46% and 52%, respectively) with no significant difference between their relative weights (mean difference: 0.03; 95% confidence interval: −0.049 to 0.114). Conclusion: Among youth with ASD, high levels of EBPs impair daily functioning as much as autistic symptoms. Systematic detection and management of EBPs may improve functioning and outcomes in youth with ASD.